Globalization and Cultural Identity in Australia - Senjov-Makohon, N. (Народна творчість та етнологія, 2019)
The article is dedicated to the cultural identity and globalization of Ukrainians who have arrived in Australia from two distinct areas of Europe to form a Ukrainian community, which has existed there for over 70 years. У статті йдеться про культурну ідентичність та глобалізацію українців, які прибули до Австралії з двох різних регіонів Європи, щоб сформувати українську спільноту, яка відтоді існує там уже понад 70 років.